Network Project Activities and Digital Tools for their Implementation - A. A. Belolobova (Открытое образование (Москва))
The paper considers the evolution of project activities and the impact of modern technologies on the form of project presentation. Features of the network project are considered, digital tools that are suitable for organizing network activities are described. The stages of project organization and digital tools for conducting a telecommunication project are described, as well as the features of creating a website for a network educational project. The article offers a description of the network project “Internet Safety”. The purpose of this article is to describe a method for creating a modern telecommunication project based on modern cloud and network tools. Based on this goal, the following tasks can be identified: • Consider the evolution of project activities. • Review the stages of project development. • Analyze modern digital tools that are suitable for transferring educational activities to the Internet. To pick up modern tools for the implementation of the network project. • Identify the features of the organization of project activities in the network. • Conduct testing and draw conclusions about the work done. The relevance of this work is that the services used in the course of studying the discipline “Informatics and ICT” must constantly change to the most modern ones and demonstrate to students the relevant tools necessary for a modern graduate and specialist. Materials and methods. The conclusions are based on a theoretical analysis of scientific and methodological literature on the use of the project method in education. The article was prepared using the materials and conclusions made by the author when creating the website of the telecommunication project “Internet Safety”. The telecommunication project took place in 2019 (May-June) at the College of Omsk State Technical University, as part of the study of the discipline “Information Technology”. Conclusion. The modern telecommunication project has a number of distinctive features. The process of preparing for the launch of the project is quite time-consuming and requires sufficient digital literacy from the teacher. The use of modern educational environments can make the process of organizing and conducting a project as comfortable as possible for all project participants. The analysis of modern educational tools, based on the description of the key features of the telecommunication project, allowed us to offer fairly easy-to-use services that can fully take advantage of network project activities. The proposed services were tested as part of the network project “Internet Safety”. As part of the research, a method of telecommunication projects has been developed and tested, which, thanks to the use of modern services, is capable of not only acquainting students with the topic of the project, but also developing the ICT competence of students, as well as increasing students' interest in studying modern technologies and improving the ability to navigate the information space. Results. The method of telecommunication projects is an effective pedagogical technology that has found a new life in the digital age. A modern project carried out on the Internet has a number of features, but due to the fact that this type of work is based on modern services and technologies, we can say that it develops the ICT competence of students and their skills to work in the network.